371 Topographical Anatomy of the Annulus of Zinn. (19th August 2022) - Lacey, Hester; Oliphant, Huw; Smith, Claire; Koenig, Michael; Rajak, Saul
Abstract: Aim: The anatomy and even existence of a common tendinous origin of the extraocular eye muscles, or annulus of Zinn, has widely been debated in anatomical literature. This study explored the anatomical origins of the recti muscles, their course into the orbit and the dural connections of the common tendinous origin with the skull base. Method: Twenty orbits of ten adult human cadavers were dissected. The orbital apex and its dural connections were photographed. Histological examination of apical specimens was performed. Results: In all cadavers, extraocular muscles were observed to have a common tendinous origin at the orbital apex, continuous with dural connections extending into the skull base. Accessory slips of the medial rectus were observed across all cadavers. Dual heads of the lateral rectus were observed in fourteen orbits of seven cadavers. The origin of the levator palpebrae superioris appeared to be contiguous with the superior rectus at the common tendinous origin in all but one cadaver. Conclusions: These results support the existence of a common tendinous origin of the extraocular muscles, that is continuous with the skull base dura. In addition, they support the existence of variations in orbital anatomy including dual or accessory muscle slips of the extraocular muscles.